2022
DOI: 10.1021/acs.est.2c02450
|View full text |Cite
|
Sign up to set email alerts
|

Improved and Reduced Performance of Cu- and Ni-Substituted Co3O4 Catalysts with Varying CoOh/CoTd and Co3+/Co2+ Ratios for the Complete Catalytic Oxidation of VOCs

Abstract: The Co3O4 spinel is one of the most promising transition metal oxide (TMO) catalysts for volatile organic compound (VOC) treatment. Substituting effects have usually been utilized to improve the catalytic performance of the Co3O4 spinel. In this study, Cu- and Ni-substituted Co3O4 catalysts derived from mixed metal–organic frameworks (MMOFs) retained similar spinel structures but exhibited improved and reduced performance for o-xylene oxidation, respectively. Physicochemical characterization and DFT calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…The catalytic performance of the Cu-and Ni-substituted Co 3 O 4 for o-xylene oxidation was related to the reducibility and oxygen mobility. 42 As shown in Figure 2C, the Cu-substituted catalyst (CuCo 2 O 4 ) presented better catalytic activity and stability. A partial electron was transferred from Co 2+ to Cu 2+ with stronger electronic affinity or from Ni 2+ to the more electrophilic Co 3+ through the adjacent lattice oxygen, causing an increase and decrease in the Co 3+ /Co 2+ molar ratio, respectively.…”
Section: Adjusting Adsorption and Desorption Of Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic performance of the Cu-and Ni-substituted Co 3 O 4 for o-xylene oxidation was related to the reducibility and oxygen mobility. 42 As shown in Figure 2C, the Cu-substituted catalyst (CuCo 2 O 4 ) presented better catalytic activity and stability. A partial electron was transferred from Co 2+ to Cu 2+ with stronger electronic affinity or from Ni 2+ to the more electrophilic Co 3+ through the adjacent lattice oxygen, causing an increase and decrease in the Co 3+ /Co 2+ molar ratio, respectively.…”
Section: Adjusting Adsorption and Desorption Of Pollutantsmentioning
confidence: 99%
“…(D, E) Oxygen vacancy formation for the MCo 2 O 4 catalysts. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Long-term Durabilitymentioning
confidence: 99%
“…The intensity of the broadened peak around 682 cm –1 for v Co -Co 3 O 4 /CC obviously increases, which can be associated with the change in the long-range order of the crystal, indicating that more defect sites are formed on v Co -Co 3 O 4 /CC . The binding energies at 682 and 192 cm –1 are attributed to the octahedral sites (CoO 6 ) and tetrahedral coordination (CoO 4 ) of the crystalline Co 3 O 4 phase, respectively. , The intensity ratio of Raman peaks ( I 192 / I 682 ) is computed to assess the proportion of CoO 4 /CoO 6 . The I 192 / I 682 ratio of v Co -Co 3 O 4 /CC (0.62) increases compared with Co 3 O 4 /CC (0.51), indicating that Al 3+ preferentially occupied the octahedral sites of Co 3 O 4 , further demonstrating that the etching of Al 3+ leads to Co 3+ vacancy.…”
Section: Resultsmentioning
confidence: 95%
“…45,46 The intensity ratio of Raman peaks(I 192 /I 682 ) is computed to assess the proportion of CoO 4 /CoO 6 . The I 192 /I 682 ratio of v Co -Co 3 O 4 /CC (0.62) increases compared with Co 3 O 4 /CC (0.51), indicating that Al 3+ preferentially occupied the octahedral sites of Co 3 O 4 , further demonstrating that the etching of Al 3+ leads to Co 3+ vacancy.…”
mentioning
confidence: 99%
“…The spinel CoMn 2 O 4 achieved a 100% conversion of toluene at only 220 °C, which was attributed to the larger surface area, rich cationic vacancies, and high mobility of oxygen species. Very recently, Ma et al 305 reported Cu- and Ni-substituted Co 3 O 4 spinel catalysts, namely MCo 2 O 4 (M = Cu or Ni), utilizing mixed metal organic frameworks as the precursor, which exhibited significantly altered performance for o -xylene oxidation. The results of XPS and XANES displayed the low oxidation state of Cu ions and high oxidation state of Ni ions, which resulted in the increased Co 3+ /Co 2+ ratio in CuCo 2 O 4 and the decreased Co 3+ /Co 2+ ratio in NiCo 2 O 4 , demonstrating the various electron transfers between Cu(Ni) atoms and Co atoms in MCo 2 O 4 .…”
Section: Tmos For Voc Oxidationmentioning
confidence: 99%